Acceptability of azithromycin for the control of trachoma in Northern Tanzania - Desmond, Nicola (Trans R Soc Trop Med Hyg, 2005)
Trachoma causes blindness; the prevention strategy includes mass antibiotic treatment. In a community in Northern Tanzania offered mass treatment with azithromycin for the control of trachoma, we used focus group discussions, individual interviews, questionnaires and direct observation to quantify, explore and contextualise reasons for acceptance or refusal. In the village studied, 76% of the population eligible to receive azithromycin were treated. Uptake was significantly higher amongst women (79% treated) than men (72%). Factors affecting acceptability included local prevention norms (such as the belief that injections, rather than oral medicine, should be used for prevention); perceptions of drugs in general and azithromycin in particular; perceptions of the distribution team’s expertise; witnessing adverse effects in others; and the timing, quality and quantity of information about azithromycin and its availability. Familiarity with trachoma as a blinding disease was significantly associated with uptake. Individuals who refused treatment seemed to be less altruistic than other respondents. Neither socio-economic status nor use of traditional healers was related to uptake. Pre-distribution community assessment and community education, advance notice of the distribution, standardised distribution guidelines and improved distributor training are recommended to maximise acceptance of azithromycin in future campaigns.